2016
DOI: 10.1177/0956462416630675
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycoplasma genitalium in men with urethritis and in high risk asymptomatic males in Tel Aviv: a prospective study

Abstract: We sought to investigate the prevalence of Mycoplasma genitalium, Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis in men presenting to a sexually transmitted infection (STI) clinic, with special attention to M. genitalium, its occurrence in Israeli patients, coinfections, and risk factors. In a cross-sectional study, 259 men were successively enrolled in the Tel Aviv Levinsky Clinic for STIs between November 2008 and November 2010. There were 118 men with urethritis and 141 high-risk me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
13
0
2
Order By: Relevance
“…These prevalence rates are similar to those found in men with objective NGU from recent series: 16.7% in London [ 4 ] and 11.9% in Tel Aviv [ 16 ]. In Amsterdam, prevalence in men reporting symptoms of urethritis was 5.9%.…”
Section: Discussionsupporting
confidence: 89%
“…These prevalence rates are similar to those found in men with objective NGU from recent series: 16.7% in London [ 4 ] and 11.9% in Tel Aviv [ 16 ]. In Amsterdam, prevalence in men reporting symptoms of urethritis was 5.9%.…”
Section: Discussionsupporting
confidence: 89%
“…Literature review for polymicrobial urethritis showed that majority of the studies are about the coexistence of both GU and NGU pathogens (16,17). However, coexistence of GU-NGU pathogens was detected only in 17.3% our patients.…”
Section: Discussionmentioning
confidence: 78%
“…Высокая эффективность азитромицина при цервицитах, обусловленных C. trachomatis, уретритах, обусловленных C. trachomatis и M. genitalium [3-5, 19, 20, 26], ранее позволяли относить азитромицин к препаратам первой линии выбора при указанных ИППП. В настоящее время приведены многочисленные доказательства роста резистентности к азитромицину [24,25,27].…”
Section: Discussionunclassified
“…В исследовании T. Gottesman и соавт. [25], проведенном в Тель-Авиве, подчеркнута необходимость обследования пациентов с негонококковыми уретритами на наличие M. genitalium, так как поражения, обусловленные этим возбудителем, характеризуются недостаточным эффектом при назначении доксициклина и возможным его отсутствием при назначении азитромицина.…”
Section: резистентность Neisseria Gonorrhoeae к азитромицинуunclassified